Optimization of a Photovoltaic Pumping System Using a Modified ABC Algorithm - Ballouti, Abdelkarim; Chouiekh, Mohamed; Ameziane, Hatim; HASSANE, LATRACH; Mourabit, Youness El; Zakriti, Alia (International Conference on Electronics, Computers and Artificial Intelligence (Online), 2025)
The renewable energy sector continues to deliver sustainable solutions for critical industrial applications, particularly in water pumping systems. Our research introduces an enhanced Artificial Bee Colony (ABC) optimization approach specifically designed to boost the performance of solar-powered pumping systems. Through comprehensive MATLAB simulations of a complete PV system incorporating a three-phase induction motor and DC-DC boost converter, our modified ABC algorithm successfully achieved exceptional 98% maximum power point tracking efficiency. The system demonstrates remarkable torque stabilization capabilities while reliably maintaining consistent pump flow rates. These significant improvements clearly establish the advantages of our proposed method over conventional MPPT approaches. The findings strongly support the practical potential of ABC-based optimization in renewable energy applications, presenting industries with an effective and dependable sustainable energy solution.